THE CHARACTERISTICS OF SEA SURFACE TEMPERATURE AND SALINITY IN SOUTH CENTRAL VIETNAMESE WATERS - Tac, Vu Van (Vietnam Journal of Marine Science and Technology, 2017)
The analyzed results of the characteristics of sea surface temperature and sea surface salinity in South Central Vietnamese waters based on MODIS and VOS data sources have revealed the variation of sea surface temperature and sea surface salinity in high ranges. Study results show that the average value of sea surface salinity ranges from 30 psu to 34 psu and is relatively stable. However, the weather is very harsh: Deviation between the highest and lowest values of sea surface temperature is 13.9°C in the seasons and that in months is 11.14°C. This is a very high amplitude, indicating the large variation of daily, monthly and seasonal temperature. The study results will help scientists and aqua-farmers take rational decisions in the selection of suitable species for aquaculture, biodiversity and environmental protection in South Central Vietnamese waters.